Studies on Bioactive Components of Red Ginseng by UHPLC-MS and Its Effect on Lipid Metabolism of Type 2 Diabetes Mellitus - Huang, Rensong; Zhang, Meng; Tong, Yu; Teng, Yaran; Li, Hui; Wu, Wei (Frontiers in Nutrition, 2022)
Objectives: Red ginseng is a processed product of Panax ginseng C.A. Meyer, which is one of the widely used medicinal and edible herbs for the treatment of Type 2 Diabetes Mellitus (T2DM). Ginsenosides are its main pharmacologically active ingredient. This study aims to clarified the material basis of total ginsenosides of red ginseng (RGW), and verify the activity of RGW in treating lipid metabolism disorders caused byT2DM. Methods: An ultra-high performance liquid chromatography coupled with quadrupole time of flight mass spectrometry (UHPLC-Q-TOF-MS) technology was applied to quantitatively analyze ginsenosides of red ginseng (RGW). T2DM rat model was established to verify the activity of RGW in treating lipid metabolism disorders caused by diabetes. First, the changes of diabetes-related parameters were observed, then the biochemical parameters of the rat serum and liver were measured, and finally the pathological sections of the rat liver were observed, and the content of short-chain fatty acids in stools were measured. The in vitro activity of RGW was verified by fatty degenerated HepG2 cells. Results: A total of 10 ginsenosides were identified and quantitatively analyzed in RGW. Experimental results demonstrated that RGW can improve lipid metabolism disorders. RGW significantly reduced the fasting blood glucose, TG and TC levels in T2DM rats, and hepatic steatosis was significantly ameliorated. In vitro experiment by RGW treatment also significantly attenuated lipid deposition in HepG2 cells. RGW up-regulated the content of 5 short-chain fatty acids in rat stools which are related to lipid oxidation and liver gluconeogenesis. Conclusion: The total ginsenosides of red ginseng were quantitatively analyzed by UHPLC-MS and its effect on lipid metabolism of T2DM was studied. Experiment demonstrated that red ginseng can regulate lipid metabolism and improve lipid deposition, which provides a promising development for red ginseng as a functional food.